Pattern of consumption of psychoactive substances in alternative transport drivers - Fernanda Branco (Instituto Politécnico de Viseu, 2020)
Introduction: Alternative transport drivers, better known as “pirates / pirateiros”, are constantly exposed to various situations that are harmful to health, such as the consumption of psychoactive substances.